2005
DOI: 10.1007/s11661-005-0291-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carbides on fatigue characteristics of austempered ductile iron

Abstract: Crack initiation and growth behavior of an austempered ductile iron (ADI) austenitized at 800 °C and austempered at 260 °C have been assessed under three-point bend fatigue conditions. Initiation sites have been identified as carbides remaining from the as-cast ductile iron due to insufficient austenization. The number of carbides cracking on loading to stresses greater than 275 MPa is critical in determining the failure mechanism. In general, high carbide area fractions promote coalescence-dominated fatigue c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
1
9
0
1
Order By: Relevance
“…Larger cracks shield the tips of smaller cracks from the applied stress until the latter become non-propagating [26]. The fatigue crack growth of larger cracks does not appear to be significantly affected by the presence of smaller cracks, which has been one of the features of these experimental results (Fig.…”
Section: Crack Growth Behaviourssupporting
confidence: 53%
“…Larger cracks shield the tips of smaller cracks from the applied stress until the latter become non-propagating [26]. The fatigue crack growth of larger cracks does not appear to be significantly affected by the presence of smaller cracks, which has been one of the features of these experimental results (Fig.…”
Section: Crack Growth Behaviourssupporting
confidence: 53%
“…It was concluded that the coarser lath size and large amounts of retained austenite promoted by the 400°C austemper promote a more tortuous crack path, and intrinsic crack shielding [18]. We have also shown that a carbide initiated failure mechanism is dominant for another ADI alloy austenitised at 800°C and austempered at 260°C due to significant numbers of brittle carbides remaining from insufficient austenitising [19]. Obviously the combination of alloying composition together with the austenitisation and austempering heat treatments, determines the microstructure produced and subsequently the dominant fatigue failure mechanisms [18,20,21].…”
Section: Introductionmentioning
confidence: 73%
“…Boundaries between "ausferrite" (bainite) packets (shown in the centre of region A of The number of fatigue cycles to failure of the same ADI material austenitised at 800°C and austempered at 260°C ('800/260') in a previous study [19] has been compared with the current results ('900/390') in Fig. 3.…”
Section: Crack Propagationmentioning
confidence: 91%
“…Where initiation processes were very easy (e.g. cracking of multiple carbides [32]]) subsequent crack growth was observed to be extremely slow, as the closely neighbouring cracks robbed surrounding crack tips of the required strain fields to propagate and lifetime was effectively controlled by coalescence events. In some cases a microcracking field can occur ahead of the crack tip, contributing significantly to crack propagation resistance [33].…”
Section: Effect Of Oxidation On Fatigue Lifementioning
confidence: 99%